CONCEPÇÕES DE MATEMÁTICA DE PROFESSORES EM FORMAÇÃO: outro olhar sobre o fazer matemático - Castro, Raimundo Santos de (2009)
In this study, it is analyzed the conceptions of Mathematics sustained by students of the last period of the course of Degree in Mathematics of the Federal Center of Technological Education of Maranhão, thirst São Luis, and their implications for the pedagogic practice of the future mathematical educator. For his accomplishment of this research was ruled in the qualitative approach, once this has for concern basic to bring the present reality the study object in a dynamic social reality, intextualizando relationships, interactions and implications proceeding of that. For so much, it was made use of the semi-structured interview while methodological procedure. The historical constitution of the teacher's of Mathematics formation is characterized in Brazil, trying to identify the conception of present Mathematics in their phases. It is discussed the Mathematical Education, the Philosophy of the Mathematical Education and the foundations of the school Mathematics, his teaching and her learning. Identifies to the light of the Philosophy of the Mathematics, of the Philosophy of the Mathematical Education, of the History of the Mathematics and of the Mathematical Education, the conceptions of Mathematics sustained by the conclusive students of the Course of Degree in Mathematics of CEFET-MA. Finally, search to discuss and to analyze the possible implications of the conceptions of Mathematics for the educational practice of the future mathematical educator. The reflection about the teacher's conceptions and on the current social practices of such conceptions it can point us the roads for the search of improvements of the teaching that will bring impacts the learning of the and in the Mathematics. In the perceptions of the totality of the subject of the research, some exist points that converge for a Mathematics of specific sense, difficult, disentailed of the external world to her. This sends us to the understanding that there is an absolutist inclination in their conceptions regarding the theme in subject. However, a change perspective appears while horizon. Being, therefore, possible to affirm that the conceptions concerning the Mathematics, his teaching and her learning, sustained by the students come in transition period of an absolutist conception for one that takes into account the produced mathematical knowledge while to know human and with significant applicability in the social contexts out of the school.